Accuracy evaluation of an X-ray microtomography system. (June 2016) - Fernandes, Jaquiel S.; Appoloni, Carlos R.; Fernandes, Celso P.
Highlights: We verify the accuracy of microtomograph with nylon lines with known diameter. The microtomographic system showed excellent results for the standard used. Excellent reproducibility for each sample section was observed. Abstract: Microstructural parameter evaluation of reservoir rocks is of great importance to petroleum production companies. In this connection, X-ray computed microtomography (μ-CT) has proven to be a quite useful method for the assessment of rocks, as it provides important microstructural parameters, such as porosity, permeability, pore size distribution and porous phase of the sample. X-ray computed microtomography is a non-destructive technique that enables the reuse of samples already measured and also yields 2-D cross-sectional images of the sample as well as volume rendering. This technique offers an additional advantage, as it does not require sample preparation, of reducing the measurement time, which is approximately one to three hours, depending on the spatial resolution used. Although this technique is extensively used, accuracy verification of measurements is hard to obtain because the existing calibrated samples (phantoms) have large volumes and are assessed in medical CT scanners with millimeter spatial resolution. Accordingly, this study aims to determine the accuracy of an X-ray computed microtomography system using a Skyscan 1172 X-ray microtomograph. To accomplish this investigation, it was used a nylon thread set with known appropriate diameter inserted into a glass tube. The results for porosity size and phase distribution by X-ray microtomography were very close to the geometrically calculated values. The geometrically calculated porosity and the porosity determined by the methodology using the μ-CT was 33.4 ± 3.4% and 31.0 ± 0.3%, respectively. The outcome of this investigation was excellent. It was also observed a small variability in the results along all 401 sections of the analyzed image. Minimum and maximum porosity values between the cross sections were 30.9% and 31.1%, respectively. A 3-D image representing the actual structure of the sample was also rendered from the 2-D images.